DIFFERENCES IN PATIENT SATISFACTION REGARDING NURSES’ THERAPEUTIC COMMUNICATION IN CLASS I, II, AND III IN PATIENT ROOMS AT RSUD SUBANG - Aulia, Maya Rahma; Fauziyah, Nuridha; Adiutama, Novian Mahayu (Universitas Airlangga, 2024)
Introduction: Therapeutic communication is one of the factors that contribute to patient satisfaction, which is a measure of the quality of the services provided by the health care provider. The objective of the investigation is to determine whether there is a disparity in patient satisfaction regarding the therapeutic communication of nurses among the nursing facilities of Classes I, II, and III at RSUD Subang. Methods: This quantitative investigation employs a cross-sectional design. The sampling technique employed is stratified sampling, with a total sample of 86 respondents involved in the sample collection. The research instrument uses a patient satisfaction questionnaire with 7 questions that require the nurses to fill in directly in the paper to assess the therapeutic communication of nurses. Results: Based on data collected by RSUD Subang's official Instagram page, @rsudsubang, the Community Satisfaction Index during the 2023 period was 83.8%. The bivariate analysis showed a p-value of 0.094, which is higher than 0.05. Subsequently, the statistical test of p > 0.05 (p-value 0.094) proves that there are no gaps in patient contentment among the hospital rooms of classes I, II, and III at RSUD Subang. Conclusions: The research is anticipated to generate data that can be employed as guidance and evaluation tools for hospitals, particularly in class I, II, and III nursing rooms, to enhance therapeutic communication in health services for patients in those classes.